Towards a Universal Translator: Decoding the PTMs That Regulate Orthoflavivirus Infection - Hannah M. Schmidt; Stacy M. Horner (Viruses)
Post-translational modifications (PTMs) serve as critical regulators of protein function across biological systems, including during viral infection. For orthoflaviviruses, including human pathogens like dengue, Zika, and West Nile viruses, PTMs on viral proteins regulate multiple aspects of the viral lifecycle and pathogenesis. Here, we review the mechanisms by which PTMs regulate orthoflavivirus infection in both vertebrate and arthropod hosts. We examine how ubiquitination and glycosylation on the viral envelope proteins facilitate viral entry and how phosphorylation, SUMOylation, and acetylation on non-structural proteins modulate viral RNA replication. Additionally, we describe how PTMs on viral structural proteins dynamically regulate viral assembly and egress. We also describe how PTMs can influence tissue tropism and host-specific pathogenesis, with some modifications showing divergent functions between arthropod vectors and vertebrate hosts, and how the host antiviral response can trigger specific PTMs on viral proteins to restrict infection, highlighting PTMs as key mediators of host-pathogen interactions. While significant progress has been made in identifying PTMs on viral proteins, many questions remain about their temporal dynamics, mechanisms of action, and conservation across the orthoflavivirus genus. Understanding how PTMs regulate orthoflavivirus infection may reveal new therapeutic strategies, particularly given recent advances in targeting specific protein modifications for disease treatment.